Constitutional origins, structure, and change in federal countries - Kincaid, John, 1946-; Tarr, G. Alan (George Alan) (Published for Forum of Federations and International Association of Centers for Federal Studies by McGill-Queen's University Press, 2005)
Annotation Providing examples of diverse forms of federalism, including new and mature, developed and developing, parliamentary and presidential, and common-law and civil law, the comparative studies in this volume analyse government in Australia, Belgium, Brazil, Canada, Germany, India, Mexico, Nigeria, Russia, South Africa, Switzerland, and the United States. Each chapter describes the provisions of a constitution, explains the political, social, and historical factors that influenced its creation, and explores its practical application, how it has changed, and future challenges, offering valuable ideas and lessons for federal constitution-making and reform.
Keywords: Federal government.; Constitutional history.; Comparative government.; Fédéralisme.; Histoire constitutionnelle.; Institutions politiques comparées.; federations.; comparative politics.; POLITICAL SCIENCE -- Government -- State & Provincial.; POLITICAL SCIENCE -- Constitutions.; Comparative government; Constitutional history; Federal government; Föderalismus